The Application of Rapid Upper Limb Assessment (RULA) for Designing a Lab-scale Flexible Conveyor - Basirun Chaniago; Sufiyanto Sufiyanto; Lilia Trisyathia Quentara (Jurnal Teknik Mesin, 2021)
The limited area of laboratory space (3000 x 3000 mm) triggered the importance of designing a flexible conveyor to support practicum activities. The process design of flexible conveyor consist of 1) Planning and preparation of product specifications; collection of product ideas based on needs and material selection. 2) Designing concepts; product dimensions with anthropometric data approach eg. elbow height, forward knee height and hand grip distance. 3) Product design; schemes or sketches that are developed into products or technical objects. 4) Pictures and specifications of product manufacture; complete review of all product elements with geometry, dimensions and material. The Rapid Upper Limb Assessment (RULA) method is used to analyze product function by investigating disorders of the upper limbs consisting of group A; upper arm, forearm, wrist, and wrist rotation, then group B; neck, torso, and feet, which are measured by the degree of injury risk. From the anthropometry approach a flexible conveyor specification was obtained with a length of 2000 mm, a width of 610 mm, a minimum height of 544 mm, and a maximum height of 957 mm. The results of the final score assessment of the standing posture and sitting position that the RULA action category is 4, with a small level of risk and for action to take some time to come.